2018
DOI: 10.1007/s11469-018-9985-6
|View full text |Cite
|
Sign up to set email alerts
|

“There Are Things I Want to Say But You Do Not Ask”: a Comparison Between Standardised and Individualised Evaluations in Substance Use Treatment

Abstract: There has been an increasing call for service users to be more actively involved with the evaluation of treatment outcomes. One strategy to impove such involvement is to ask service users to contribute with their own criteria for evaluation by sharing their personal story and perspective about their clinical situation. In this cross-sectional study, we contrasted the contents elicited by service users completing two individualised measures against the contents of three widely used standardised measures. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…This result is similar to Alves et al. (2020), which found that almost half (49%) of the participants seeking treatment for substance abuse identified a key problem or difficulty not measured by three standardised PROMs: the CORE‐OM, The Patient Health Questionnaire‐9 (PHQ‐9; Kroenke, Spitzer, & Williams, 2001) and the substance‐use‐specific Treatment Outcomes Profile (TOP; Marsden et al., 2008). However, our findings were less pronounced than previous work by Sales et al.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This result is similar to Alves et al. (2020), which found that almost half (49%) of the participants seeking treatment for substance abuse identified a key problem or difficulty not measured by three standardised PROMs: the CORE‐OM, The Patient Health Questionnaire‐9 (PHQ‐9; Kroenke, Spitzer, & Williams, 2001) and the substance‐use‐specific Treatment Outcomes Profile (TOP; Marsden et al., 2008). However, our findings were less pronounced than previous work by Sales et al.…”
Section: Discussionsupporting
confidence: 84%
“…However, in contrast to our study and that of Alves et al. (2020), only two PROMs were used for comparison, neither of which was disease specific. It appears that, as the number of PROMs increases, and with the inclusion of both universal PROMs (e.g., CORE‐OM, PHQ‐9) and disease‐specific PROMs (e.g., EDE‐Q, TOP), the number of unique concerns identified by the PSYCHLOPS decreases.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Measuring outcomes must be of clinical utility and not just a tick-box process (Wolpert et al, 2014). Clinical judgement in the type of measurement which may suit and be useful for work with the individual is key and the advice is to use client-defined measures alongside other measures of outcome (Alves et al, 2018; Green, 2016; Wolpert et al, 2014). Training in the process of measuring outcomes and how to use them to enhance SDM may be of as much importance, if not more, as deciding which outcome measures to use.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there is also some research which suggests that goal-based outcome measures may align more to functioning aspects of personal change, as opposed to symptomatology, thus further suggesting that they may be most appropriately used alongside other measures of outcome (Jacob, Edbrooke-Childs, et al, 2017). Indeed, the use of both broad, standardised measures and personalised outcome measures is encouraged to ensure that a breadth of information is considered (Alves et al, 2018; Green, 2016; Wolpert et al, 2014). This also links to research which suggests that the clinical utility of outcome measurement is of most importance and the mindful use of outcome measures is key to their use (Wolpert et al, 2014).…”
Section: Making Outcome Measures Countmentioning
confidence: 99%